Question and Answers Forum

All Questions      Topic List

Integration Questions

Previous in All Question      Next in All Question      

Previous in Integration      Next in Integration      

Question Number 201172 by Calculusboy last updated on 01/Dec/23

Answered by Sutrisno last updated on 01/Dec/23

=∫((2e^(2x) −e^x )/( (√(3(e^(2x) −2e^x −(1/3))))))dx  =(1/( (√3)))∫((2e^(2x) −e^x )/( (√((e^x −1)^2 −(4/3)))))dx  misal : e^x −1=(2/( (√3)))secθ→tanθ=((√(3e^(2x) −6e^x −1))/2)                  dx=(2/( (√3))).((secθ.tanθ)/e^x )dθ=(2/( (√3)))(((secθ.tanθ)/((2/( (√3)))secθ+1)))dθ  =(1/( (√3)))∫((2((2/( (√3)))secθ+1)^2 −((2/( (√3)))secθ+1))/( (√(((2/( (√3)))secθ)^2 −(4/3))))).(2/( (√3)))(((secθ.tanθ)/((2/( (√3)))secθ+1)))dθ  =(1/( (√3)))∫((2((2/( (√3)))secθ+1)−1)/( (2/( (√3))).tanθ)).(2/( (√3))).secθtanθdθ  =(1/( (√3)))∫(4/( (√3)))sec^2 θ+secθdθ  =(1/( (√3)))((4/( (√3)))tanθ+ln∣secθ+tanθ∣)  =(1/( (√3)))((4/( (√3)))((√(3e^(2x) −6e^x −1))/2)+ln∣(((√3)(e^x −1))/2)+((√(3e^(2x) −6e^x −1))/2)∣)+c

=2e2xex3(e2x2ex13)dx=132e2xex(ex1)243dxmisal:ex1=23secθtanθ=3e2x6ex12dx=23.secθ.tanθexdθ=23(secθ.tanθ23secθ+1)dθ=132(23secθ+1)2(23secθ+1)(23secθ)243.23(secθ.tanθ23secθ+1)dθ=132(23secθ+1)123.tanθ.23.secθtanθdθ=1343sec2θ+secθdθ=13(43tanθ+lnsecθ+tanθ)=13(433e2x6ex12+ln3(ex1)2+3e2x6ex12)+c

Commented by Calculusboy last updated on 04/Dec/23

thanks sir

thankssir

Terms of Service

Privacy Policy

Contact: info@tinkutara.com